Navigating the Challenges of COVID-19: A Guide for Mental and Behavioural Health - Sangeeta Kakkar; Ashu Kumari (International Journal of Behavioral Sciences, 2025)
The COVID-19 epidemic has posed unique encounters globally, impacting various aspects of daily life, including mental and behavioral health. The present study attempts to prepare a guide with ways and means to navigate the challenges of the COVID-19 pandemic. This guide provides comprehensive insights and strategies for individuals to navigate these challenges effectively. The study began by addressing the psychosomatic effect of the pandemic, such as increased anxiety, depression, PTSD, OCD, and feelings of isolation. The guide discussed the prominence of acknowledging and validating these emotions while offering coping mechanisms like mindfulness, relaxation techniques, and maintaining social connections virtually. Furthermore, the guide investigated the behavioral changes brought about by the pandemic, such as disruptions in routines, sleep patterns, and coping mechanisms. It emphasized the significance of establishing new routines and upholding a healthful regime by practicing activities like acceptance and mindfulness exercises, art therapy, and guided imagery to cater to the cognitive domain. In contrast, nutrition through a healthy diet and regular practice of yoga asanas will help to enhance the physical, and biological domain of an individual. This will safeguard whole advancement and inculcate resilience and adaptive coping for an individual when facing an adverse situation. In conclusion, this guide served as a worthy resource for people who look for to prioritize their mental and behavioral well-being within the ongoing commitments of the COVID-19 pandemic. Urgently reorganizing psychological health services for rural populations,policymakers, healthcare providers, and community stakeholders is essential to meeting unmet demands now and preparing for obstacles in the post-pandemic future. By implementing the strategies outlined in this guide, individuals can nurture resilience, adaptability, and holistic well- being during these uncertain times.
Keywords: COVID-19; Challenges; Mental health; behavioural health; emotional health